2015
DOI: 10.1016/j.drugalcdep.2015.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis, cigarettes, and their co-occurring use: Disentangling differences in default mode network functional connectivity

Abstract: Background Resting-state functional connectivity is a noninvasive, neuroimaging method for assessing neural network function. Altered functional connectivity among regions of the default-mode network have been associated with both nicotine and cannabis use; however, less is known about co-occurring cannabis and tobacco use. Methods We used posterior cingulate cortex (PCC) seed-based resting-state functional connectivity analyses to examine default mode network (DMN) connectivity strength differences between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 58 publications
(71 reference statements)
5
38
1
1
Order By: Relevance
“…Tobacco users showed lower connectivity between the PCC and temporal, mPFC (ventral ACC and medial orbitofrontal cortex (mOFC)) and cerebellar (crus I/II) regions and enhanced PCC-cerebellar (bilateral lobule VIIIB) and PCC-mPFC (bilateral frontal poles) connectivity. Cannabis and tobacco users only showed lower PCC-temporal cortex connectivity[40]. The authors proposed that the observed alterations in DMN connectivity were related to addiction more generally and as such might represent an underlying neurobiological vulnerability associated with substance use.…”
Section: Neural Correlates Of Cannabis and Tobacco Usementioning
confidence: 99%
“…Tobacco users showed lower connectivity between the PCC and temporal, mPFC (ventral ACC and medial orbitofrontal cortex (mOFC)) and cerebellar (crus I/II) regions and enhanced PCC-cerebellar (bilateral lobule VIIIB) and PCC-mPFC (bilateral frontal poles) connectivity. Cannabis and tobacco users only showed lower PCC-temporal cortex connectivity[40]. The authors proposed that the observed alterations in DMN connectivity were related to addiction more generally and as such might represent an underlying neurobiological vulnerability associated with substance use.…”
Section: Neural Correlates Of Cannabis and Tobacco Usementioning
confidence: 99%
“…Currently, we are only aware of one study that examined combined vs. unique associations of cannabis and nicotine on resting state networks (RSNs). Using a seed-based analysis that focused on posterior cingulate gyrus (PCG) connections in the brain’s default mode network (DMN), Wetherill and colleagues (2015) found decreased connectivity in users of only cannabis, only nicotine, and concurrent users compared to non-using controls (Wetherill et al 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Corresponding to the literature on cannabis use and resting-state temporal correlation and network spatial maps, cannabis use was associated with the DMN (Bossong et al, 2013; Pujol et al, 2014; Wetherill et al, 2015), a network implicated in self-referential thought, social perspective taking, future thought, and memory (Andrews-Hanna, 2012), and the ECNs (Houck et al, 2013). Interestingly, Pujol et al (2014) showed that the association between activation of the DMN and memory was stronger in young adult cannabis users compared to controls.…”
Section: Discussionmentioning
confidence: 96%